Upaya Meningkatkan Kesadaran Peserta Didik Dalam Mematuhi Tata Tertib Sekolah di SMK Negeri 1 Surakarta Melalui Pembelajaran PPKn - Theresia Tri Hartanti (Publikasi Indonesia, 2023)
The purpose of this study was to determine the role of PPKn as an educational tool in increasing students' awareness of complying with school rules at SMKN 1 Surakarta for the 2023/2024 academic year. This research is descriptive qualitative. Source of data using primary and secondary. Data collection techniques through interviews, observation and documentation. In order for the data to be valid, source and technique triangulation was carried out. Analyzed using interactive qualitative techniques. Based on the data analysis, it can be concluded: The role of PPKn as a means of legal education in increasing awareness of the rights and obligations of students is indeed true, such as getting facilities. The role of PPKn as a means of legal education in increasing awareness of students' attendance is indeed true, such as being present on time. The role of PPKn as a means of legal education in raising awareness of the neatness of students is indeed like being in full uniform. PPKn's role as a means of legal education in raising students' hygiene awareness is indeed true, it is like participating in community service activities.